The debate concerning deviance and divergence: A new theoretic proposal - Germán Silva-García; Angélica Vizcaíno-Solano; Bernardo Pérez-Salazar (Oñati Socio-Legal Series, 2024)
This article discusses theoretical questions related to the notion of social deviance, a concept that has been a pillar of criminology and sociology since the mid-20th century. We argue that social deviance is not equipped with adequate analytic devices to satisfactorily describe social actions labelled as transgressions. This discussion reconsiders the notion of social deviance, recasting its theoretical significance and use in the field of criminology. In its place, we advance the category of social divergence, highlighting its greater analytical power to address social actions that trigger penal control interventions. Social divergence is a novel conceptual contribution in the tradition of the sociology of conflict. Its purpose is to offer an analytical model of social conflicts and their inner workings as key elements to describe, analyze and improve our understanding of their interactions with penal control systems from a criminological perspective.